The Degree of Application Classroom Teachers to Procedural Knowledge in Mathematics Based on Marzano’s Model "A field Study at Basic Education Schools in the City of Lattakia" - القاضي, لمى (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study aimed at investigating the degree of application classroom teachers to procedural knowledge in mathematics based on Marzano’s Model, and to investigate the effect of experience and qualification on the degree of application procedural knowledge in Mathematics. For that, the descriptive method was used, and prepared a reliable validate questionnaires’ the degree of application classroom teachers to procedural knowledge in mathematics based on Marzano’s Model. The simple random sample consisted of (97) teachers in Lattakia City schools. The results showed that the degree of application classroom teachers to procedural knowledge in mathematics was low in general, and its sub-domain of (Construct Model, Shape, Internalize, and Evaluation) based on Marzano’s Model was low. In addition, there were significant differences among teachers` experience on the application of procedural knowledge in Mathematics in favor of experience since (10) years old more. There were no significant differences due to the qualification of the degree of application procedural knowledge in Mathematics. So, the research recommended in the light of the results of study to Necessity improve of the preparation programs of classroom teachers in the education faculties for development of learning outcomes in Mathematics.